Learning Leadership in a Changing World Virtue and Effective Leadership in the 21st Century - McCloskey, M. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Learning Leadership in a Changing World provides direction and support in the form of the 4R Model of Leadership—a theoretically sound, conceptually straightforward, and educationally powerful framework.